Farm diversification as a potential success factor for small-scale farmers constrained by COVID-related lockdown. Contributions from a survey conducted in four European countries during the first wave of COVID-19 - Benedek, Zsófia; Fertő, Imre; Galamba Marreiros, Cristina; Aguiar, Pâmela Mossmann de; Pocol, Cristina Bianca; Čechura, Lukáš; Põder, Anne; Pääso, Piia; Bakucs, Zoltán (PloS one, 2021)
This paper explores to what extent product and marketing channel diversification contributed to the economic success of small-scale agricultural producers involved in short food supply chains after the outbreak of the COVID-19 pandemic. A survey was conducted between April and July 2020 in four countries of the European Union-Estonia, Hungary, Portugal and Romania,-resulting in a relatively large sample of farmers (N = 421). The analysis was built on a semi-nonparametric approach. Approximately 19 percent of small-scale producers were able to increase sales during the first wave of the pandemic, although country-level variation was significant. Fruits and vegetables were by far the most popular products. The importance of specific channels varied across countries, but farm gate sales were among the most important marketing channels both before and during the first wave. The importance of channels that were based on digital resources and home delivery increased. Our evidence indicates that diversification was a strategy that paid off, both in terms of marketing channels and different product categories. However, the impact appears to be nonlinear; the initial advantage generated by diversification rapidly tapered off, either temporarily (in the case of products), or permanently (in the case of marketing channels). Later research may clarify whether these findings are generalizable in other socio-economic contexts, as well as in a non-COVID situation.
Keywords: ekonomické modely; Evropa; Quarantine; zemědělství; průzkumy a dotazníky; COVID-19; karanténa; Humans; zemědělci; Farmers; Surveys and Questionnaires; Europe; Agriculture; lidé; Models, Economic